1997
DOI: 10.1002/(sici)1097-0142(19970515)79:10<1944::aid-cncr15>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone induces apoptosis and up-regulation of p53 expression in human ovarian carcinoma cell lines

Abstract: METHODS. Antiproliferation effects of PROG on 3AO and AO ovarian carcinomaShanghai Institute of Cell Biology, Chinese cells were determined by 3 H-thymidine incorporation. Apoptosis of the PROGAcademy of Sciences, Shanghai, China. treated cells was determined by DNA laddering analysis and was quantitated by both nuclear condensation and flow cytometry after cells were stained with propidium iodide. Cell cycle analysis was also performed by flow cytometry. The expression of p53, bcl-2, and c-myc after 72 hours … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(66 citation statements)
references
References 26 publications
(4 reference statements)
3
63
0
Order By: Relevance
“…In humans, circulating androstenedione was found to be positively associated with ovarian cancer risk (32). Several experimental studies indicate a protective effect for progesterone on ovarian carcinogenesis through apoptotic mechanisms (35)(36)(37).…”
Section: Offspring Gender and Maternal Risk Of Ovarian Cancer Cancer mentioning
confidence: 99%
“…In humans, circulating androstenedione was found to be positively associated with ovarian cancer risk (32). Several experimental studies indicate a protective effect for progesterone on ovarian carcinogenesis through apoptotic mechanisms (35)(36)(37).…”
Section: Offspring Gender and Maternal Risk Of Ovarian Cancer Cancer mentioning
confidence: 99%
“…in vitro and in vivo (6)(7)(8)(9). Taken together, these facts suggest ways in which natural P4 might function as a chemotherapeutic agent against neurogenic tumors such as neuroblastoma.…”
Section: Introductionmentioning
confidence: 96%
“…A handful of studies have demonstrated that progestins inhibit cell growth and/or induce apoptosis in OCa cell cultures (Bu et al, 1997;Hu and Deng, 2000;Keith and Bonavida, 2001;Yu et al, 2001;Syed and Ho, 2003). Alterations in apoptosis regulators such as bcl-2, c-myc, and p53 were detected in OCa cells undergoing progestin-induced apoptosis (Bu et al, 1997;Hu and Deng, 2000;Athanassiadou et al, 1998). Relatively high doses of progestins (1 mM range) were used in these studies to achieve growth inhibition and apoptosis.…”
Section: Introductionmentioning
confidence: 99%